Ammonia stress reduces antibiotic efflux but enriches horizontal gene transfer of antibiotic resistance genes in anaerobic digestion. (January 2020) - Zhang, Junya; Buhe, Chulu; Yu, Dawei; Zhong, Hui; Wei, Yuansong
Graphical abstract: Highlights: Ammonia stress significantly influenced the fate of ARGs in anaerobic digestion. Ammonia stress reduced ARGs associated with antibiotic efflux. Ammonia stress enriched ermB by the enhancement of horizontal gene transfer. The fate of nitrogen cycling genes response to ammonia stress is clarified. Horizontal gene transfer caused by ammonia stress contributed most to ARGs directly. Abstract: The dynamics of antibiotic resistance genes (ARGs) response to ammonia stress were evaluated using metagenomics and quantitative PCR (qPCR) in anaerobic digestion (AD). Ammonia stress reduced ARGs associated with antibiotic efflux, especially the major facilitator superfamily (MFS) of tet(L), due to free ammonia (FA) that changed the proton gradient of efflux system. Nonetheless, ARGs of antibiotic target alteration, especially ermB, were enriched under ammonia stress, which could be attributed to the initiation of the internal enhancer of the transferability of the broad host range plasmid, pAMbeta1. Statistical analysis elucidated the significant changes of ARGs are directly attributed to the mobile genetic elements (MGEs), but the little affected ARGs are mainly determined by the functional microbes reflected by nitrogen cycling genes (NCyc). This study deciphered the profiles of ARGs response to ammonia stress in AD, which indicated the importance of alleviation of ammonia inhibition for the mitigation of ARGs dissemination.